Teacher and Student Opinions on Teaching Four Operations with Integer Numbers in 7th Grade with Counting Stamps - Süzen, Ahmet Burak; Tutak, Tayfun; İlhan, Aziz; Nayıroğlu, Büşra (Tamer KUTLUCA, 2024)
The study examines the views of middle school mathematics teachers and 7th-grade students on using counting stamps to teach four operations with integers. The study was conducted with ten mathematics teachers with different professional seniority and ten 7th-grade students studying in these schools. The teachers were asked six open-ended opinion form questions, and the students were simultaneously asked five open-ended opinion form questions. In this qualitative study, the interview technique was used to analyze the views of teachers and students. A structured interview form was preferred as a data collection tool. A qualitative research method was adopted in collecting, analyzing, and interpreting the data of this study. Content analysis was used to analyze and interpret the data. According to the study results, it was determined that teachers and students did not find counting stamps functional and that they needed to be more adequate in operations with integers. Therefore, there is a need for new models that can replace counting stamps.

The study examines the views of middle school mathematics teachers and 7th-grade students on using counting stamps to teach four operations with integers. The study was conducted with ten mathematics teachers with different professional seniority and ten 7th-grade students studying in these schools. The teachers were asked six open-ended opinion form questions, and the students were simultaneously asked five open-ended opinion form questions. In this qualitative study, the interview technique was used to analyze the views of teachers and students. A structured interview form was preferred as a data collection tool. A qualitative research method was adopted in collecting, analyzing, and interpreting the data of this study. Content analysis was used to analyze and interpret the data. According to the study results, it was determined that teachers and students did not find counting stamps functional and that they needed to be more adequate in operations with integers. Therefore, there is a need for new models that can replace counting stamps.
Teacher and Student Opinions on Teaching Four Operations with Integer Numbers in 7th Grade with Counting Stamps
Keywords: Mathematics Education; Matematik Eğitimi